2019
DOI: 10.3390/nu11071508
|View full text |Cite
|
Sign up to set email alerts
|

Nut and Peanut Butter Consumption and Mortality in the National Institutes of Health-AARP Diet and Health Study

Abstract: Although previous studies have shown inverse associations between nut consumption and mortality, the associations between nut consumption and less common causes of mortality have not been investigated. Additionally, about 50% of peanut consumption in the US is through peanut butter but the association between peanut butter consumption and mortality has not been thoroughly evaluated. The National Institutes of Health-AARP (NIH-AARP) Diet and Health Study recruited 566,398 individuals aged 50–71 at baseline in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Additionally, in spite of a similarly low average nut consumption in Korea, a recent large cross-sectional population survey relating dietary factors to all-cause and cause-specific mortality using a comparative risk assessment analysis found that a sizable proportion of deaths was related to low consumption of nuts [ 63 ]. The results of a recent very large ( n = 566,398) population-based prospective study in the US with a median follow-up of 15.5 years support the inverse association between higher nut consumption and total mortality (HR = 0.78; 95% CI, 0.76, 0.81); in contrast consumption of peanut butter was not associated with lower risk of mortality [ 27 ]. Finally, the recent report from the PURE study described a significant reduction in total mortality (HR = 0.77; 95% CI, 0.69, 0.87) for highest (≥120 g/week) versus lowest (<30 g/month) nut consumption [ 28 ].…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, in spite of a similarly low average nut consumption in Korea, a recent large cross-sectional population survey relating dietary factors to all-cause and cause-specific mortality using a comparative risk assessment analysis found that a sizable proportion of deaths was related to low consumption of nuts [ 63 ]. The results of a recent very large ( n = 566,398) population-based prospective study in the US with a median follow-up of 15.5 years support the inverse association between higher nut consumption and total mortality (HR = 0.78; 95% CI, 0.76, 0.81); in contrast consumption of peanut butter was not associated with lower risk of mortality [ 27 ]. Finally, the recent report from the PURE study described a significant reduction in total mortality (HR = 0.77; 95% CI, 0.69, 0.87) for highest (≥120 g/week) versus lowest (<30 g/month) nut consumption [ 28 ].…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 95%
“…In these cohorts, only tree nuts, not peanuts, were associated with reduced CVD outcomes. In a very large ( n = 566,398) population-based prospective study in the US with a median follow-up of 15.5 y, data on cause-specific mortality confirmed the inverse association between higher total nut consumption and CVD deaths (Hazard Ratio [HR], 0.70; 95% CI, 0.66, 0.74), while no association for peanut butter consumption was found [ 27 ]. The Prospective Urban and Rural Epidemiology (PURE) study, conducted in 16 countries from 5 continents, examined nut consumption in relation to CVD outcomes in 124,329 participants followed for a median of 9.5 y [ 28 ].…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 99%
“…Yer fıstığının kolesterol ve trans yağ içermemesine ek olarak doymuş yağ asiti oranının düşük olması sebebiyle dünyada en çok mortalite nedeni olan kardiyovasküler hastalıklarda (KVH) tüketiminin güvenilir olduğu düşünülmektedir [64]. Amba ve ark [65] [66]. Yapılan başka bir çalışmada ise bireyler üç gruba ayrılmış, birinci grubun herhangi bir diyet kısıtlaması yapmadan diyetlerine ilave 500 kilokalori yer fıstığı tüketmesi, ikinci grubun diyet tedavisine ek olarak 500 kilokalori yer fıstığı tüketmesi, üçüncü grubun ise günlük toplam yağ alımını yer fıstığından karşılaması istenmiştir.…”
Section: Kardiyovasküler Hastalıklar Ve Yer Fıstığıunclassified
“…They provide not only a rich source of unsaturated fatty acids, high-quality protein, arginine, vitamin E, and other antioxidants [3], but also value via the phytonutrient composition (carotenoid, stilbenes, lignans, phenolic aldehydes flavonoids, and phytosterols) [1,4,5]. Due to these health benefit properties [6], peanut is recognized to reduce risks of cardiovascular disease (CVD) [7][8][9], complications of diabetes mellitus (DM) [10], cancer [11,12], and cognitive dysfunction [13]. Therefore, peanuts are widely consumed roasted or boiled, and also processed into various forms such as butter, candy, chocolates, cakes, beverages, and others.…”
Section: Introductionmentioning
confidence: 99%